2021
DOI: 10.3390/mi12091086
|View full text |Cite
|
Sign up to set email alerts
|

Method for QCM Resonator Device Equivalent Circuit Parameter Extraction and Electrode Quality Assessment

Abstract: Quartz crystal microbalance (QCM) resonators are used in a wide range of sensors. Current QCM resonators achieve a simultaneous measurement of multiple physical quantities by analyzing lumped-element equivalent parameters, which are obtained via the introduction of external devices. This introduction of external devices will probably increase measurement error. To realize the measurement of multiple physical quantities while eliminating the measurement error caused by external devices, this paper proposes a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The Butterworth–Van Dyke (BVD) model illustrated in Figure 4 a is often employed to characterize the electro-acoustic impedance behavior of the QCM sensors [ 27 , 28 , 29 ]. , , , and are related to the additional capacitance between the two electrodes, mechanical flexibility, initial mass, and energy dissipation of the QCM sensor, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Butterworth–Van Dyke (BVD) model illustrated in Figure 4 a is often employed to characterize the electro-acoustic impedance behavior of the QCM sensors [ 27 , 28 , 29 ]. , , , and are related to the additional capacitance between the two electrodes, mechanical flexibility, initial mass, and energy dissipation of the QCM sensor, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It can be found that the peak frequency ( ) of the conductance curve of each sensor decreases and the HBW widens as the humidity increases. The equivalent circuit parameters and Q values of the ChNF-integrated QCM sensors were obtained from the conductance and susceptance [ 27 ], as shown in Table 2 . As shown in Figure 4 f, the equivalent resistance ( ) of all ChNF-integrated QCM humidity sensors increases with increasing humidity.…”
Section: Resultsmentioning
confidence: 99%
“…Each technique presents its own trade-offs in terms of cost, application specificity, accuracy, and measurement duration. Importantly, the interaction between measurement devices and quartz crystals is crucial, as front-end electronics can introduce loading effects, influencing measurement accuracy [ 22 , 23 ]. In fact, despite the exceptional sensitivity and resolution offered by quartz electromechanical resonators, they also exhibit significant sensitivity to front-end electronics loading and parasitic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Surface-sensitive acoustic methods are rather useful for analysis of various processes [25]. They can also be used for detection of protease activity because they do not require any labeling of the substrate [26].…”
Section: Introductionmentioning
confidence: 99%